If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 4 = 246 Reorder the terms: 4 + 2w = 246 Solving 4 + 2w = 246 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2w = 246 + -4 Combine like terms: 4 + -4 = 0 0 + 2w = 246 + -4 2w = 246 + -4 Combine like terms: 246 + -4 = 242 2w = 242 Divide each side by '2'. w = 121 Simplifying w = 121
| X+1=-13 | | -2/7x-4 | | x+2=y+1 | | r^2-1/(2r)-1/2 | | 2(x+2)+58=8x-6(x-5) | | 3x^2+23x-12=0 | | -3+2/7 | | 4a-75=a | | r^2-1/2r-1/2 | | x+40=100 | | z+75=z-7/4 | | g(x)=log(x-6) | | z+7/5=z-7/4 | | 1*2/19=19y | | 88+x/2=90 | | n-46=32 | | 3x-6=-8x+6+7x | | 14=-4(y-3)-3 | | 2/19=19y | | -(3y+3)-(-2y-6)=-1 | | 1/3(10x-6)=8 | | 6p-32-35=5 | | x+5=56 | | 3x^2+14x+31=0 | | x-2/2x^2-9x+10=0 | | -4x^2-11x-6=0 | | 1/2(c+8)=1/4c | | 2x-24=6x | | 8x+82=3x+2 | | 6ln(x^2-3)-7=12.2 | | 7+18r-3=6r+64-3r | | -12x-114=5x+11+8x |